THE COMUNITYSTRUCTURE OF EPIPHYTIC DIATOMS ON SEAGRASS LEAVES OF (Thalassia hemprichii) IN NIRWANA BEACH WATERS OF PADANG CITY,WEST SUMATERA PROVINCE - Riski Hambali; Zulkifli Zulkifli; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in March 2018. The purpose of this research was to determine the water quality, the structure of epiphytic diatoms community in Nirwana Beach Padang City, West Sumatra Province. The method used were consisting of field survey.Identification and analysis of epiphytic diatoms was conducted at Marine. Biology Laboratory Faculty of Fisheries and Marine University of Riau.Based on the results of the study,the abundance of epiphytic diatoms ranged between 7.077 ind/cm2 - 22.155 ind/cm2, diversity index (H ') ranged from 1,4325 - 1,8315 (medium category), uniformity index (E) ranged from 0,6482 - 0,7110 means the uniformity of organisms in the waters of Nirwana Beach is in a stable state, and dominance index (C) ranged from 0,4042 - 0,5111 . it can be said that there are types that dominate at station III. The identification found 9spesies of epiphytic diatoms i.e.: Melosirasp., Coscinodiscussp., Cocconeissp., Diploneissp., Gyrosigmasp., Naviculasp., Pleurosigmasp., Nitzschiasp. danRhizosoleniasp. The most common type and has the highest abundance is Cocconeis sp. and Nitzschi sp.Keywords: Community Structure, Epiphytic Diatoms, Thalassia hemprichii,Nirwana Beach